Evolution of dispersion along the extruder during the manufacture of polymer-organoclay nanocomposites - Barbas, J. M. (2013)
Although correlationsbetweenthe final dispersionleveloforganoclaynanocompositesandmeltmixing conditions inatwinscrewextruderhavebeenproposed,theactuallengthwiseevolutionofdispersionin these machinesisstillnotwellunderstood.Despitetheirpracticalimportancesuchstudiesaredifficult, due tothepossibilityofinducingdegradationand/ormorphologychangesduringmaterialcollection and/or samplepreparation.Thisworkuseson-linerheometryandin-linenear-infraredspectroscopy (NIR) tomonitortheevolutionofdispersionofaPP/PP-g-MA/organoclaysystemalongtheaxisoftwin screwextruder.Regardlessofthescrewprofile utilised,dispersiondevelopsquicklyinthe first partofthe machine, andthenitlevels-offordecreases,evenifthe final dispersionlevelsaresignificant. Inorderto validatethisdata,ScanningTransmittedElectronMicroscopy(STEM),X-raydiffraction(XRD)andmid- FT-IRanalysesarecarriedoutonsamplescollectedfromthesamelocationswheretheon-line/in-line measurements wereperformed.Theresultsconfirmed thepreviousmeasurements.Thermogravimetric analysis(TGA)andTimeofFlight-SecondaryIonMassSpectrometry(TOF-SIMS)onclay,matrixand nanocomposite showedthatthermaldegradationoftheclaysurfactantandofthepolymermatrixcould contribute totheobserveddispersionreversal.